Fading of VHF cordless telephone received signals - Huang, Leh Huong. (2009)
A study of the radio propagation characteristics of a cordless telephone, in the lower VHF band of 49.3 MHz, is carried out in this project. The cordless telephone is modified to obtain a varying dc output which is proportional to the received radio frequency signal level. The received signal is data-logged and analysed to investigate how the signals vary in different environment. Two different environments are chosen -the open field and the office environments. In both the environments, the path loss characteristics, the probability density function and the cumulative density function distributions and the slow and the fast fading of the received signals are analysed and discussed. Further analyses of the received signal in the office environment includes penetration losses across the wall and the floor and the temporal variations of the received signals due to people passing by the cordless telephone.